Comprehensive Analysis of the Potential Immune-Related Biomarker Transporter Associated With Antigen Processing 1 That Inhibits Metastasis and Invasion of Ovarian Cancer Cells - Li, Xiaoxue; Zeng, Shiyu; Ding, Yiling; Nie, Yanting; Yang, Mengyuan (Frontiers in Molecular Biosciences, 2021)
Transporter associated with antigen processing 1 (TAP1) is a protein related immune regulation and plays a role in several malignant tumors. However, the effect of TAP1 on immune infiltration, immunotherapy, and metastasis in different cancers has not been reported till date. The cancer genome atlas database, the tumor immune estimation resource (TIMER) database, and the estimation of stromal and immune cells in malignant tumors using expression (ESTIMATE) algorithm were used to determine the correlation between TAP1 expression and the prognosis of a variety of cancers, immune infiltration, immune checkpoint genes, DNA methylation, and neoantigens. Various enrichment analyses were used to study the correlation between TAP1 and key transcription factors using the Kyoto encyclopedia of genes and genomes (KEGG) pathway in ovarian cancer. Immunological methods were used to evaluate the expression of TAP1 protein in ovarian and cervical cancer, and Kaplan–Meier analysis was used to analyze the prognostic value of TAP1. RNA interference (RNAi) was used to verify the effect of TAP1 on ovarian cancer. Compared with normal tissues, cancer tissues showed a significant increase in the expression of TAP1, and TAP1 expression is related to the poor prognosis of cancers such as ovarian cancer. The expression level of TAP1 is correlated with immune checkpoint genes, DNA methylation, tumor mutation burden, microsatellite instability, and neoantigens in various cancers. Our results showed that TAP1 was upregulated in patients with ovarian cancer cell lines and was associated a with poor prognosis. Further, we verified the expression of TAP1-related transcription factors (MEF2A and LEF1) and found that TAP1 is closely related to ovarian cancer metastasis. These results indicate that TAP1 can be used as a biomarker for the diagnosis and prognosis of cancer and as a new therapeutic target.